Letter from the United States Department of State to Ernst Berl, April 7, 1943 - United States. Department of State; Hackworth, Green Haywood (1943)
Letter from Green H. Hackworth (1883-1973), a legal advisor with the United States Department of State, to Ernst Berl (1877-1946) regarding his property in Germany.
Keywords: United States. Department of State; Berl, Ernst, 1877-1946; Real property--Foreign ownership--Government policy; Hackworth, Green Haywood, 1883-1973